2012
DOI: 10.1111/j.1476-5381.2012.01846.x
|View full text |Cite
|
Sign up to set email alerts
|

A prolyl oligopeptidase inhibitor, KYP‐2047, reduces α‐synuclein protein levels and aggregates in cellular and animal models of Parkinson's disease

Abstract: BACKGROUND AND PURPOSE The aggregation of α‐synuclein is connected to the pathology of Parkinson's disease and prolyl oligopeptidase (PREP) accelerates the aggregation of α‐synuclein in vitro. The aim of this study was to investigate the effects of a PREP inhibitor, KYP‐2047, on α‐synuclein aggregation in cell lines overexpressing wild‐type or A30P/A53T mutant human α‐syn and in the brains of two A30P α‐synuclein transgenic mouse strains. EXPERIMENTAL APPROACH Cells were exposed to oxidative stress and then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 57 publications
(70 reference statements)
5
106
2
2
Order By: Relevance
“…It was previously shown that PREP accelerates aSyn aggregation and that a PREP inhibitor blocks this in vitro and promotes clearance of aSyn aggregates in aSyn-overexpressing cells and in vivo models (14,22). However, although PREP increased the aggregation of aSyn in a cell-free model, the interaction between PREP and aSyn has not been documented earlier.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…It was previously shown that PREP accelerates aSyn aggregation and that a PREP inhibitor blocks this in vitro and promotes clearance of aSyn aggregates in aSyn-overexpressing cells and in vivo models (14,22). However, although PREP increased the aggregation of aSyn in a cell-free model, the interaction between PREP and aSyn has not been documented earlier.…”
Section: Discussionmentioning
confidence: 78%
“…The PREP inhibitor, KYP-2047 (4-phenylbutanoyl-l-prolyl-2(S)-cyanopyrrolidine), was synthesized in the School of Pharmacy, University of Eastern Finland, as previously described (25). KYP-2047 was chosen as a reference compound because the biochemical and pharmacological data indicate that it is potent and selective, enters cells in culture, and crosses the blood-brain barrier effectively in rodents (22,24,26,27).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations